1998
DOI: 10.1111/j.1751-0813.1998.tb12337.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid neoplasia in the koala

Abstract: The prognostic value of an immunophenotypic, anatomical and morphological basis for the classification of lymphoid neoplasia in the koala currently is limited by the need to detect these neoplasms at an early age, the requirement for freshly fixed tissues and the restricted range of available cross-reacting antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
16
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 13 publications
(26 reference statements)
4
16
0
Order By: Relevance
“…The ability of GALV and SSV to cause neoplasia in their host species has been demonstrated in both natural (28,54,56) and experimental infections (12,29). In view of the relatively high prevalence of hematopoietic neoplasia and related diseases in koalas (4,11,61) and anecdotal evidence for lymphoid neoplasia epizootics in captive koala colonies, it is reasonable to suspect a pathogenic role for KoRV. However, KoRV was detected in all diseased and healthy koalas tested and appears to be endogenous.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of GALV and SSV to cause neoplasia in their host species has been demonstrated in both natural (28,54,56) and experimental infections (12,29). In view of the relatively high prevalence of hematopoietic neoplasia and related diseases in koalas (4,11,61) and anecdotal evidence for lymphoid neoplasia epizootics in captive koala colonies, it is reasonable to suspect a pathogenic role for KoRV. However, KoRV was detected in all diseased and healthy koalas tested and appears to be endogenous.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoid malignancy is a relatively common disease of both free-living and captive koalas (11,55), and its clinical similarity to retrovirus-associated disease in other mammals has been noted (7,24). The ability of GALV and SSV to cause neoplasia in their host species has been demonstrated in both natural (28,54,56) and experimental infections (12,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD3, CD5, and CD79b were used in the previous study [4,5]. However, the effectiveness of the markers Oct-2, kappa light chains, CD138, and PAX5 has not been demonstrated in koalas.…”
mentioning
confidence: 99%
“…Since 1961, various authors have reported isolated cases of spontaneous lymphoid neoplasia in both captive and free-ranging koalas [1,5,6]. The previous study described that the 19 of the 51 lymphoma cases were extranodal lymphomas likely originated from stomach, intestine, spleen, liver, brain, lungs, and conjunctiva [5].…”
mentioning
confidence: 99%